Preparation and Characterization of Polysulfone/Celullose Acetate (PSF/CA) Blend Membrane - Syahbanu, Intan; Piluharto, Bambang; Khairi, Syahrul; Sudarko, S.; Hermanto, Toto (Jurnal ILMU DASAR, 2019)
Blend polysulfone (PSF)/cellulose acetate (CA) membranes have prepared by phase inversion method. In here, CA was prepared from bacterial cellulose by acetylation reaction. Various temperature of coagulation bath were used as variable to investigated water uptake, water flux, porosity and thermal properties of membranes. As comparison, the CA commercial (CCA) was also investigated with the same parameters. As the result, the functional group analysis by FTIR show that CA has successfully prepared from bacterial cellulose. The parameters include water uptake, water flux and porosity have the similar trend. The parameters increase with increasing of temperature of coagulation bath. The other hand, CCA membrane have similar trend to CA membranes for parameter of water water uptake, water flux and porosity. However, CCA membrane is higher than CA membranes for all parameters. Thermal analysis by Differential Scanning (DSC) showed that all blend membranes with different temperature of coagulation bath have single transition glass temperature (Tg) that indicated that molecular homogeneity. Keywords: blend membrane, phase inversion, coagulation bath, water flux, porosity.